Ecofisiologia tritícola - Souza, Emerson de Freitas Cordova de [UNESP]; Silva, Marcelo de Almeida [UNESP] (My University, 2013)
There are many studies about wheat crop in Brazil. Most of them involve factors related directly to productivity, such as cropping systems, fertilization and pest control and diseases. Although they are not taken into account concerning issues about the results of such crop, since the environmental conditions affect its cycle. The knowledge about wheat ecophysiology and ecological factors have influenced on wheat development. Climatic conditions (temperature, humidity and photoperiod) and abiotic influences such as biostimulation use and plant growth regulators are essential for producers to know cultural practices in detail as well as which crops managements should be done in a certain phenological stage of the plant. Thus, this literature review aims to present the main features of wheat in different growth stages during its crop cycle, including plant anatomy and ecological factors that influence its development. Therefore, the reflection occurs in the final yield of the crop. So, the answer is reflected in crop yield.

Há muitos estudos referentes à cultura do trigo no Brasil. A maioria envolve fatores ligados diretamente à produtividade, tais como sistemas de plantio, adubação e controle de pragas e doenças, porém, não são levadas em conta as questões sobre as respostas da cultura, haja vista as condições ambientais afetarem seu ciclo. O conhecimento sobre a ecofisiologia da cultura bem como os fatores ecológicos interferem no desenvolvimento dessa cultura. São exemplos as condições climáticas (temperatura, umidade e fotoperíodo) e influências abióticas como o uso de bioestimulantes e de reguladores vegetais fundamentais para que os produtores possam saber detalhadamente quais tratos culturais devem ser feitos em determinado estádio fenológico da planta. Assim, há a diminuição das perdas na produção, no plantio e colheita da cultura sob cuidados adequados e em datas corretas a fim de amenizar, ao máximo, a dependência de outros países para o abastecimento interno. Com isto, o objetivo desta revisão bibliográfica é apresentar as principais características do trigo nos diferentes estádios fenológicos durante o ciclo da cultura, incluindo a anatomia da planta e os fatores ecológicos que interferem em seu desenvolvimento. Portanto, o reflexo surge na produtividade final do cultivo.
Wheat ecophysiology
Keywords: Triticum aestivum L.; Yield environment; Physiology; Development stages; Management; Triticum aestivum L.; Ambiente de produção; Fisiologia; Estádios de desenvolvimento; Manejo